Efficient Preparation of α-Aminoboronic Acid Derivatives via Boroalkyl Group Migration - Zajdlik, Adam; He, Zhi; St Denis, Jeffrey D.; Yudin, Andrei K. (Synthesis, 2014)
A reaction demonstrating migration of boron-substituted carbon is presented. It is shown that α-boroalkyl groups of transient boroalkyl acyl azide intermediates migrate readily from carbon to nitrogen. This transformation allows access to a novel class of stable molecules, α-boryl isocyanates, from easily preparable α-borylcarboxylic acid precursors. The protocol enables the synthesis of a diverse range of α-aminoboronic acid derivatives, including α,α-disubstituted analogues.
Keywords: boron; isocyanates; Curtius rearrangement; boroalkyl shift